Conflicting regional policy goals: accessibility and segregation in the Helsinki metropolitan area - Katriina Rosengren; Timo M. Kauppinen; Johanna Lilius; Jarkko Rasinkangas; Hannu Ruonavaara (Urban, Planning and Transport Research)
Regional land use, housing, and transport (MAL) agreements between the Finnish state and municipalities in growth regions guide urban policy in the Helsinki metropolitan area towards regional cooperation and densification. Alongside economic growth and connectivity goals, segregation prevention is a visible but ill-defined social sustainability goal in these agreements, and anti-segregation measures lean heavily on providing new social housing in accessible locations. This tool, in turn, leans on a combination of social mixing, a traditional preventive tool in fighting segregation, and a new tool, maximising spatial justice through transit-oriented development. We argue that there is a discrepancy between these goals: while on an individual level, public transport accessibility is meant to reduce transport poverty and provide equal opportunities for employment and services, accessible areas fare lower than others in socioeconomic status. Therefore, increasing social rental housing in areas with lower socioeconomic status may unintentionally amplify segregation. This article asks how actors of different governance levels view concentrating social housing in accessible locations as a risk to segregation. Interviews show a concern of social challenges not being sufficiently addressed.